EKSPLORASI HISAB GERHANA MATAHARI MENGGUNAKAN ALGORITMA MEEUS - Akhyar, Andi Muh.; Fatmawati, Fatmawati; Nasyori, Achmad (ELFALAKY: Jurnal Ilmu Falak, 2021)
The solar eclipse will take place if the moon is between the Earth and sun as well as its shadow touches the Earth. Some hadiths narrated that the phenomena had occurred in the era of Prophet saw. then He commanded Muslims to perform prayer, remembrance, and donation. Hence, the solar eclipse in Islam is crucial as it is respected to worship to God. The objective of this paper is to calculate the solar eclipse using Meeus Algorithm. After preparing the Bessel elements and arranging the Meeus Algorithm, it can be determined accurately both the eclipse type, time, place, path width of the eclipse and the sun position as it lasts. Sun eclipse calculation using Meeus algorithm on June, 21th 2020 results 1.380 N and 18.060 E for the coordinate, 0.28 for altitude, azimuth of 66.56, 84.9 km width, as well as total duration of 1 minutes 22.3 and seconds. Those all are accurate due to the similarity with NASA calculation using ELP and VSOP87 algorithm.